De Dom Casmurro à Capitu : processo e produto de uma adaptação - Santos, Uziel Moreira dos (2014)
This research consists of analyzing the adaptation of the romance Dom Casmurro, by Machado de Assis, to the television micro-series Capitu, directed by Luiz Fernand Carvalho. It is intended to expose and analyze the similarities and differences between the chosen works, as well as the choices and procedures made inside dialogues with the theory and the practice of which corresponds to the core of the adaptations. For that, it was sought to answer the following questions-problems: how to adapt the narrative elements and the literary specifics of the novel Dom Casmurro to the micro-series Capitu? How to situate the changes between the original and its mediated palimpsest, taking into consideration the dichotomous context surrounding the adaptation s phenomenon? Which procedures, employed in this adaptation, resulted into artistic possibilities to a television product? To investigate the legitimacy of such information, a revision of the studies about the analysis phenomenon was performed, as well as a television and cinematographic language norms, respecting the trans-didactic genre embedded in the micro-series Capitu. It was also analysed the way in which the narrative and the literary specifics in Dom Casmurro were worked by the director, as well as the audiovisual resources created showing the level of complexity of the reading done by the adapter over the original. In this sense, it was selected a critical-theoretical nucleus composed of the main authors: Robert Stam, Linda Hutcheon, Linda Seger, Maria Ester Maciel, Ismail Xavier. In the course of three chapters, it was arranged for the thinkers to dialog with the corpus